PIX, Open Finance, and DREX: Cases of digital public infrastructure in Brazil - Almeida, Vanessa da R.S.; Macadar, Marie Anne (Conference on Digital Government Research, 2025)
Digital Public Infrastructure (DPI) is a new concept that garnered significant attention during the 2023 G20 discussions. DPIs can help advance all United Nations Sustainable Development Goals, making research in this area critically important. Despite its significance, academic literature on DPI is still scarce. To help cover this gap, this poster proposes a DPI evaluation framework based on the United Nations' definition of DPI. The evaluation framework was applied to three potential DPI cases that emerged from the Brazilian finance sector. The selected cases include PIX, an instant payment solution; Open Finance Brazil, a consent-based data exchange solution; and DREX, the Brazilian central bank digital currency. Using the proposed evaluation framework, it was demonstrated that the first two cases can be considered DPIs, and the last one has the potential to become a DPI.